The morphological changes in the spinal motor segments of the lumbar spine after rigid spinal stabilization with implants - Dedukh, Ninel; Bengus, Lyudmila; Levshin, Oleksandr; Kosterin, Sergey; Barkov, Oleksandr; Piontkovsky, Valentyn (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Rigid implants for spinal fusion are widely used in the clinical practice. However, there are only a few studies that have examined at the tissue level reorganization of structures of the spinal unit in a fusion. Objective: to study the structural organization of the intervertebral discs, vertebrae and facet joints of the lumbar spine rabbits simulated osteochondrosis after rigid fixation. Methods: osteochondrosis modeled by nucleotomy intervertebral disc LV–LVIin rabbits using the decompressor, which was introduced via posterolateral approach to the nucleus pulposus zone under CT control. After 6 months 5 animals underwent the stabilization of the LIV–LVIspinal unit using rigid implants. 3 months after spinal unit stabilization spinal unit rabbits were sacrificed, lumbar spine was examined histologically. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> stabilization of the lumbar spine at the level of LIV<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">–LVI<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">rigid segments of the fixing device in rabbits with degeneration of the intervertebral disc has promoted its fibrotization that is considered as the positive impact of this type of fixing. Moderate degeneration of the intervertebral disc found cranial and more pronounced cranial from fixation zone. In the control group of animals recorded progression of dystrophic and destructive changes in the tissues of the disc. With rigid fixation in the bone tissue of the vertebral bodies are expressed osteoporotic changes in comparison to control animals that is caused by a decrease in the load on the vertebral segment. Also revealed the progression of osteoarthritis in the facet joints at the nucleotomy level in animals.